Controlled release fertilizer and container volumes in the production of Parapiptadenia rigida (Benth.) Brenan seedlings - Ezequiel Gasparin (Acta Scientiarum. Agronomy, 2015)
Growing demand fornative treeseedlings will require improvements in quality standards of production processes through the use of more efficient cultivation techniques. This study evaluated the effects of different doses of controlled release fertilizer (CRF) and different container volumes in the production of Parapiptadenia rigida seedlings. We examined the effects of five different concentrations (0, 3, 6, 9 and 12 g L-1 substrate) of CRF (18-5-9 NPK) and three different container volumes (50, 110 and 180 cm3) on seedling height (H) and collar diameter (CD) measured monthly for seven months and then calculated H/CD ratios. After 210 days of growth, the dry masses of the aerial portions, root systems, and total masses were determined, as well as the concentrations of macro- and micronutrients in the aerial portions of the seedlings. In general, the dose 9 g L-1 substrate combined with the 180 cm3 cultivation tubes demonstrated the best results in terms of the morphological variables analyzed, resulting in consistent quality seedlings for field planting.